Organizational Justice as a Mediator for Transformational Leadership and Work Outcomes - Wahibur Rokhman (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
AbstractThis study examined the mediating role of distributive and procedural justice in linking transformational leadership and job satisfaction, organizational commitment and turnover intention. Survey data was consisted of 370 employees from 60 institutions of Islamic microfinance in Central Java, Indonesia. The empirical tests indicated that transformational leadership has significant effect on procedural and distributive justice. Also, distributive and procedural justice has significant effect on all the three work outcomes. Furthermore, distributive justice was found to have mediation effect in the relationship between transformational leadership and organizational commitment and job satisfaction, but not for turnover intention. However, the study did not find any significant mediating effect of procedural justice on the relationship between transformational leadership and job satisfaction and turnover intention, but significant on organizational commitment. Keywords:transformational leadership, distributive justice, procedural justice, organizational commitment, job satisfaction and turnover intention.AbstrakStudi ini meneliti peran mediasi dari keadilan distributif dan prosedural dalam hubungan antara kepemimpinan transformasional dan kepuasan kerja, komitmen organisasi dan turnover intention. Survei dilakukan terhadap 370 karyawan dari 60 lembaga keuangan mikro Islam di Jawa Tengah, Indonesia. Tes empiris menunjukkan bahwa kepemimpinan transformasional memiliki pengaruh yang signifikan terhadap keadilan prosedural dan distributif. Juga, keadilan distributif dan prosedural memiliki pengaruh yang signifikan pada tiga hasil pekerjaan yakni kepuasan kerja, komitmen organisasi dan turnover intention. Selain itu, keadilan distributif ditemukan memiliki efek mediasi dalam hubungan antara kepemimpinan transformasional dan komitmen organisasi dan kepuasan kerja, tetapi tidak untuk turnover intention. Namun, studi ini tidak menemukan efek mediasi keadilan prosedural yang signifikan pada hubungan antara kepemimpinan transformasional dan kepuasan kerja dan turnover intention, tetapi signifikan pada komitmen organisasi. Kata kunci:kepemimpinan transformasional, keadilan distributif, keadilan prosedural, komitmen organisasi, kepuasan kerja dan niat omset.